Perceived Benefits of Digital Storytelling for Speaking Development Among Motivated Indonesian EFL Learners - Sulistianingsih, Endang; Fitriati, Sri Wuli; Mujiyanto, Januarius (Register Journal, 2025)
This study investigates the perceived benefits of Digital Storytelling (DST) as an instructional approach aimed at developing speaking-related competencies among highly motivated English as a Foreign Language (EFL) learners in an Islamic private university in Central Java, Indonesia, where the majority of academics are Muslims. Implementing a sequential explanatory mixed-methods design, the research combines quantitative observations of learners’ speaking activities with qualitative insights into their experiences and reflections. While the data indicate improvements in certain aspects of speaking, particularly in areas such as confidence, engagement, and idea formulation, the findings are interpreted cautiously due to the small sample size and specific contextual factors. Students reported that DST activities enhanced their motivation, reduced their anxiety, and provided them with greater autonomy in expressing themselves orally. Rather than positioning DST as a panacea for speaking fluency, the study suggests that it may serve as a complementary pedagogical tool that supports affective and cognitive dimensions of oral language learning in culturally specific EFL contexts.